"Um agricultor exemplar": linguagem avaliativa no gênero história de vida - Weber, Andréa Franciéle (2007)
The social spread of mass communication has allowed the emergence of new current textual genres. Among them, the histories of life, which are published by an agricultural cooperative journal and are read in the rural environment of the regions west, north-west and north of the state of Santa Catarina. This study aims at describing such genre, in special, the evaluative language that characterizes the histories of life. It also aims at testing the feasibility of the Appraisal Theory to be applied to the Portuguese Language and the use of computer tools to this kind of analysis. For such, a corpus of 23 pieces of histories of life published in 2005, which were analyzed under the categories of field and ideational content (Halliday, 1997), rhetorical movements (Swales, 1990) and attitude and voices in the journalistic speech (Martin e White, 2005). For complementary analysis from the histories of life reading, we applied our corpus to the tools of the software WordSmith, which provided data on the lexical frequency and terms occurrence in the linguistic context. Contextual information on the genre was gotten through interview with producers and consumers of histories of life and of the participative observation in the place of production of the journal. The results indicate that the rhetorical movements of history of life are, on one hand, strictly dependent on the production context of the interviews and, on the other hand, on the communicative objectives of the genre. The ideational content is identical in all the texts, focusing in the process of economic growth of the character. Concerning evaluative language, the histories of life mainly approach judgment rates, either explicit or implicit, based on social positive esteem, which are intensified by the use of the adverbs ever and never as well as connotative language. The most noticeable in the genre is the voice of the correspondent, in which authorial judgments of social esteem are present. This way, through these language resources, the histories of life consolidate its rhetoric objective that is to provide an example of farmer to the other farmers, aiming at the keeping the man in the countryside and the agricultural productivity increase.